1974
DOI: 10.1021/je60062a017
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-liquid equilibrium relations of binary systems propane-n-octane and butane-n-octane

Abstract: The P-p-T-x relationships of the propane-n-octane and the n-butane-n-octane systems are determined. The experimental results cover a range from about 150 lb/in.2 abs and room temperature to the highest pressure and temperature at which liquid and vapor can coexist. The data are presented in tabular form. P-T-x, p-T-x, and isobanc T-x diagrams are given.This paper presents the P-p-T-x relationships of the binary systems of propane-n-octane and n-butane-n-octane. It is the third of a series (5, 6) in a study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 1 publication
2
22
0
1
Order By: Relevance
“…. The obtained curves show typical shapes, confirming the reliability of the results where the agreement with the corresponding experimental values reported in the literature for the various considered systems is reasonable , .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…. The obtained curves show typical shapes, confirming the reliability of the results where the agreement with the corresponding experimental values reported in the literature for the various considered systems is reasonable , .…”
Section: Resultssupporting
confidence: 90%
“…The NRTL model is rather of a molecular nature and is based on the local composition concept . It requires molecular interaction parameters, which are determined in the present study from experimental phase equilibria data reported in , by minimizing the objective function F obj defined by means of Eqs. and and expressed by Eq.…”
Section: The Refrigeration Machinementioning
confidence: 99%
“…than that given by the rectilinear diameter construction in Figure 8. In Figures 10 and 11 we compare our model for CgH18-CsHg with the data of Kay et al (1974). Even with identically equal to zero, the model provides a very good description of the P-T-x and p-T-x surfaces for the mixtures, with mole fractions of propane less than about 0.8.…”
Section: Mixture Datamentioning
confidence: 93%
“…Finally, binary interaction parameters were fitted for the interactions nitrogen-oxygen, nitrogen-argon and oxygen-argon though those are of very limited practical interest for natural gas systems because argon is normally not present in natural gas compositions and oxygen is only a trace component in very few natural gas samples. However, the [60] 22 273-348 0.14-2.0 0.10-0.90 (Propane-n-pentane) [61] 97 321-461 1.0-4.5 0.14-0.88 (Propane-n-hexane) [62,63] 226 325-497 0.14-8.7 0.14-0.92 (Propane-n-octane) [64] 89 344-550 0.69-5.8 0.21-0.96 (n-Butane-isobutane) * [65] 16 288-327 0.2-0.7 0.20-0.79 (n-Butane-n-pentane) [66] 66 358-464 1.0-3.6 0.14-0.87 (n-Butane-n-hexane) [66] 68 375-502 0.6-3.9 0.10-0.90 (n-Butane-n-heptane) [67] 74 333-525 0.4-3.9 0.16-0.94 (n-Pentane-n-hexane) [68] 72 298-348 0.1-30 0.12-0.87 (n-Pentane-n-heptane) [ interaction parameters for those three interactions will allow a further test of the mixture model about the prediction of properties of air. It was mentioned in the Introduction that it is possible to form 120 binary interactions with the 16 fluids of this study.…”
Section: Fitting Of the Modelmentioning
confidence: 99%